Major Presidential Candidates Describe Tax Policies (Taxes, 2024)
Wolters Kluwer has based this briefing on what it considers accurate, nonpartisan, and unbiased information at the time of publication. ■ INDIVIDUAL TAXATION Income Tax Rates Under current law, there are seven tax brackets: 10, 12, 22, 24, 32, 35, and 37 percent, which are applicable from 2018 through 2025 under TCJA. Capital Gains/Dividends Under current law, a capital gains rate of 0 percent, 15 percent, or 20 percent applies to capital gains and qualified dividends received by individuals, depending upon the amount of the individual's taxable income. For one year, in 2021, the amount of the child tax credit was increased to $3,000 ($3,600 in the case of a child under the age of six). Since that expired, there have been several unsuccessful attempts by lawmakers in both parties to extend the higher amount beyond 2021. Earned Income Credit Under current law, the earned income credit (EIC) is available to lower-income taxpayers with earned income up to certain inflation adjusted amounts.